2014
DOI: 10.1007/s10456-014-9435-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like 7, a novel pro-angiogenetic factor over-expressed in cancer

Abstract: Angiopoietin-like (ANGPTL) proteins are secreted proteins showing structural similarity to members of the angiopoietin family. Some ANGPTL proteins possess pleiotropic activities, being involved in cancer lipid, glucose energy metabolisms, and angiogenesis. ANGPTL7 is the less characterized member of the family whose functional role is only marginally known. In this study, we provide experimental evidences that ANGPTL7 is over-expressed in different human cancers. To understand the role played by ANGPTL7 in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 35 publications
2
55
1
1
Order By: Relevance
“…Moreover, removal of ANGPTL7 with antibody restored endothelial cell proliferation, migration, and tube formation to control levels. These experiments differ from those of Parri et al, who found that recombinant ANGPTL7 augmented endothelial proliferation and migration . In our hands the same bacteria‐derived recombinant protein had no effect on the endothelial cells in any of the assays we used (http://onlinelibrary.wiley.com/doi/10.1002/hep.27838/suppinfo).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, removal of ANGPTL7 with antibody restored endothelial cell proliferation, migration, and tube formation to control levels. These experiments differ from those of Parri et al, who found that recombinant ANGPTL7 augmented endothelial proliferation and migration . In our hands the same bacteria‐derived recombinant protein had no effect on the endothelial cells in any of the assays we used (http://onlinelibrary.wiley.com/doi/10.1002/hep.27838/suppinfo).…”
Section: Discussioncontrasting
confidence: 99%
“…We found ANGPTL7 to be antiangiogenic. In general, attribution of angiogenic activities to ANGPTL7 has been inconsistent, with some studies reporting proangiogenic effects and others suggesting antiangiogenic functions . These discrepancies may be attributed to differences in assay conditions, cell types used, and species‐specific signaling.…”
Section: Discussionmentioning
confidence: 99%
“…28 Just recently, ANGPTL7 was reported to be a hypoxia-driven proangiogenetic factor upregulated in cancer cells that can induce malignant behavior in human prostate cancer cells: it could be an interesting candidate to profile across many schwannomas, to determine if its expression levels correlate with malignant progression. 29,30 Many of the upregulated genes that we identified in our study have been functionally characterized as part of the inflammatory response, a hallmark enabling characteristic that can support multiple cancer capabilities. 31 MADCAM1, another highly upregulated gene in our angiosarcoma samples, is associated with the onset and progression of multiple gastric inflammatory diseases and is also upregulated in melanoma cells.…”
Section: Discussionmentioning
confidence: 95%
“…After 12 h incubation on Matrigel at 37 °C, the plates were photographed under a phase contrast microscope. The degree of tubule formation was quantified by counting the branching points in four randomly chosen fields from each well [51]. …”
Section: Methodsmentioning
confidence: 99%